HARMONISASI ORANG TUA DAN SEKOLAH DALAM MEMBANGUN PESERTA DIDIK CERDAS DAN UNGGUL - Nurbaiti, Nurbaiti (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract—- The advancement of science and technology changes the lifestyle of people from childhood, to adults. Similarly, the effect on the pattern of education conducted by parents and schools. However sophisticated any progress of Science and Technology can not replace the function, the role of parents and teachers, especially in guarding the growth and development of learners to reach the ideals. Psychologically, in school age, learners are always looking for educators who are admired, respected, and idolized until some of the learners try to imitate the attitude, style of parents and teachers that brought in his life. Along with the desire to align the role of parents and school in the development of children is crucial. Evidence from several studies on the achievement of learning achievement of learners to be increased with the participation of parents directly and actively in the education of their children. Indicators of success as revealed by the results of Harvard Family Research Project's (HFRP) research that the involvement of parents have a close relationship with the results of achievement child. These findings consistently appear on the child's success, in the scores of grades, of the teacher's judgment. In line with the success in terms of learning achievement, the role of BK teachers becomes important when learners experience a collision in the learning process. These problems can not be left alone, the presence of school counselors (teachers BK) is needed to assist them to optimize the ability of the learners so that the harmony Keywords: Hamonization, Parent-school, counselor, smart, superior learners Abstrak— Kemajuan IPTEK mengubah lifestyle kehidupan masyarakat mulai dari kanak- kanak, hingga orang dewasa. Begitu pula pengaruhnya terhadap pola edukasi yang dilakukan oleh orang tua dan sekolah. Namun secanggih apapun kemajuan IPTEK tidak dapat menggantikan fungsi, peran orang tua dan guru khususnya dalam mengawal tumbuh dan kembang peserta didik menggapai cita- cita. Secara psikologis pada usia sekolah peserta didik senantiasa mencari figur pendidik yang dikagumi, dihormati, dan diidolakan hingga beberapa diantara peserta didik mencoba meniru sikap, gaya orangtua dan guru yang dibawanya dalam kehidupannya. Sejalan dengan keinginan untuk menyelaraskan peran orang tua dan sekolah dalam perkembangan anak sangat krusial. Dibuktikan dari beberapa penelitian tentang pencapaian prestasi belajar peserta didik menjadi meningkat dengan keikutsertaan orang tua secara langsung dan aktif dalam pendidikan anak-anaknya.Indikator keberhasilan tersebut seperti diungkap oleh hasil penelitian Harvard Family Research Project’s (HFRP) bahwa keterlibatan orangtua memiliki kaitan erat dengan hasil prestasi anak. Penemuan ini secara konsisten nampak pada kesuksesan anak, dalam skor nilai, penilaian guru. Sejalan dengan keberhasilan dalam segi prestasi belajar, peran guru BK menjadi penting manakala peserta didik mengalami benturan dalam proses pembelajaran. Permasalahan tersebut tidak dapat dibiarkan begitu saja, kehadiran konselor sekolah (guru BK) diperlukan untuk mendampingi mereka mengoptimalkan kembali kemampuan yang dimiliki oleh peserta didik sehingga keselarasan Kata Kunci— Hamonisasi, Orangtua- sekolah, konselor, peserta didik cerdas, unggul